2015
DOI: 10.2139/ssrn.2743217
|View full text |Cite
|
Sign up to set email alerts
|

International Careers of Researchers in Biomedical Sciences: A Comparison of the US and the UK.

Abstract: from the JAE-Doc "Junta para la Ampliación de Estudios" Programme that is co-financed by the Social Structure Funds (SSF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Empirical studies have shown that the United States has been a magnet for scientists from all over the world since the mid-20 th century, particularly during its hegemonic period [ 37 , 38 ], but it has continued to attract scientists also in the early 21 st century [ 39 ]. The mobility to the United States is typically motivated by better opportunities for increased productivity and/or scientific impact [ 40 , 41 ] and by career advancement [ 42 ]. Therefore, it is plausible to assume that scientists educated in strongly institutionalized environments would frequently migrate to research settings in which research organizations are less determined by their institutional environment.…”
Section: Resultsmentioning
confidence: 99%
“…Empirical studies have shown that the United States has been a magnet for scientists from all over the world since the mid-20 th century, particularly during its hegemonic period [ 37 , 38 ], but it has continued to attract scientists also in the early 21 st century [ 39 ]. The mobility to the United States is typically motivated by better opportunities for increased productivity and/or scientific impact [ 40 , 41 ] and by career advancement [ 42 ]. Therefore, it is plausible to assume that scientists educated in strongly institutionalized environments would frequently migrate to research settings in which research organizations are less determined by their institutional environment.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, two independent studies comprising U.S. and UK scientists do not find significant performance differentials across movers and nonmovers (Hunter, Oswald, and Charlton, 2009;Lawson et al 2015). Kerr and colleagues (Kerr, Kerr, and Lincoln, 2013;Kerr and Lincoln, 2010) use stochastic name matching to differentiate immigrants from non-immigrants and find no evidence of performance differentials (including patent citations and patent originality) in a large sample of U.S. inventors.…”
Section: International Mobility Innovation and Performancementioning
confidence: 96%
“…Conversely, two independent studies comprising US and UK scientists do not find significant performance differentials across movers and non‐movers (Hunter et al, ; Lawson et al ). Kerr and colleagues (Kerr and Lincoln, ; Kerr et al, ) use stochastic name matching to differentiate immigrants from non‐immigrants and find no evidence of performance differentials (including patent citations and patent originality) in a large sample of US inventors.…”
Section: International Mobility Innovation and Performancementioning
confidence: 96%